Application of AllerCatPro 2.0 for protein safety assessments of consumer products - Krutz, Nora L.; Kimber, Ian; Winget, Jason; Nguyen, Minh N.; Limviphuvadh, Vachiranee; Maurer-Stroh, Sebastian; Mahony, Catherine; Gerberick, G. Frank (Frontiers in Allergy, 2023)
Foreign proteins are potentially immunogenic, and a proportion of these are able to induce immune responses that result in allergic sensitization. Subsequent exposure of sensitized subjects to the inducing protein can provoke a variety of allergic reactions that may be severe, or even fatal. It has therefore been recognized for some time that it is important to determine a priori whether a given protein has the potential to induce allergic responses in exposed subjects. For example, the need to assess whether transgene products expressed in genetically engineered crop plants have allergenic properties. This is not necessarily a straightforward exercise (as discussed elsewhere in this edition), but the task becomes even more challenging when there is a need to conduct an overall allergenicity safety assessment of complex mixtures of proteins in botanicals or other natural sources that are to be used in consumer products. This paper describes a new paradigm for the allergenicity safety assessment of proteins that is based on the use of AllerCatPro 2.0, a new version of a previously described web application model developed for the characterization of the allergenic potential of proteins. Operational aspects of AllerCatPro 2.0 are described with emphasis on the application of new features that provide improvements in the predictions of allergenic properties such as the identification of proteins with high allergenic concern. Furthermore, the paper provides a description of strategies of how AllerCatPro 2.0 can best be deployed as a screening tool for identifying suitable proteins as ingredients in consumer products as well as a tool, in conjunction with label-free proteomic analysis, for identifying and semiquantifying protein allergens in complex materials. Lastly, the paper discusses the steps that are recommended for formal allergenicity safety assessment of novel consumer products which contain proteins, including consideration and integration of predicted consumer exposure metrics. The article therefore provides a holistic perspective of the processes through which effective protein safety assessments can be made of potential allergenic hazards and risks associated with exposure to proteins in consumer products, with a particular focus on the use of AllerCatPro 2.0 for this purpose.